2010
DOI: 10.1016/j.phytochem.2009.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Saponins and a lignan derivative of Terminalia tropophylla from the Madagascar Dry Forest

Abstract: A study of an EtOH extract obtained from the roots of the Madagascan plant Terminalia tropophylla H. Perrier (Combretaceae) led to the isolation of the new oleanane-type triterpenoid saponin 1, the new lignan derivative 2, and the two known saponins arjunglucoside I (3) and sericoside (4). The structures of the new compounds 1 (terminaliaside A) and 2 (4′-O-cinnamoyl cleomiscosin A) were elucidated using 1D and 2D NMR experiments and mass spectrometry. Compound 1 showed antiproliferative activity against the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…As stated in their report, those three novel compounds may have been artifacts formed through spontaneous oxidation and tertiary amine quaternization during plant extraction. 7) Three novel alkaloids, isohalitulin (22) and haliclorensins B (23) and C (24), together with the three known compounds halitulin, haliclorensin, and isohalicloresin, were isolated from the chloroform (CHCl 3 )-MeOH (2 : 1) extract of the Madagascan sponge Haliclona telearensis (class Demospongiae, order Haplosclerida, family Chalinidae), collected in Salary Bay, north of Tulear, Madagascar. All three new compounds were tested for their toxicity against brine shrimp, and the results indicated that all exhibited moderate activity, with LD 50 values of 0.9, 2.2, and 2.1 µM, respectively.…”
Section: Alkaloidsmentioning
confidence: 99%
See 3 more Smart Citations
“…As stated in their report, those three novel compounds may have been artifacts formed through spontaneous oxidation and tertiary amine quaternization during plant extraction. 7) Three novel alkaloids, isohalitulin (22) and haliclorensins B (23) and C (24), together with the three known compounds halitulin, haliclorensin, and isohalicloresin, were isolated from the chloroform (CHCl 3 )-MeOH (2 : 1) extract of the Madagascan sponge Haliclona telearensis (class Demospongiae, order Haplosclerida, family Chalinidae), collected in Salary Bay, north of Tulear, Madagascar. All three new compounds were tested for their toxicity against brine shrimp, and the results indicated that all exhibited moderate activity, with LD 50 values of 0.9, 2.2, and 2.1 µM, respectively.…”
Section: Alkaloidsmentioning
confidence: 99%
“…None of the compounds displayed any inhibition when tested against the A2780 human ovarian cancer cell line. 22) A novel oleanane-type triterpene saponin terminaliaside A (61), together with the two known saponins arjunglucoside and sericoside, was isolated from the MeOH fraction of the roots of the Madagascan plant Terminalia tropophylla H. PERRIER (Combretaceae) following bioassay-guided fractionation. Compound 61 exhibited moderate antiproliferative activity against the A2780 human ovarian cancer cell line, with an IC 50 value of 1.2 µM.…”
Section: Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…153 Some metabolites isolated from Terminalia species have shown a wide range of biological activities, including antimalarial, 154 antifungal, [154][155][156] antibacterial, [155][156][157] and cytotoxic activities. 153 The compounds were tested in the A2780 assay. 153 The compounds were tested in the A2780 assay.…”
Section: Pentacyclic Triterpenoidsmentioning
confidence: 99%